TINJAUAN KRIMINOLOGIS PENCURIAN DENGAN KEKERASAN MENGUNAKAN SENJATA TAJAM - Mustaqim, Adi Surya (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACT Adi Surya Mustaqim, 2019: " Violent Criminology Review Using Sharp Weapons"Community association, every day there is a relationship between members of the community with one another. The association creates various events or events that can move legal events. Theft exists because of factors of poverty, ignorance, and economic pressure that tend to make people deviate (theft). Crime problem is an eternal problem in human life, because it develops in line with the development of an increasingly complex level of human civilization. This study aims to determine the factors that cause theft with violence using sharp weapons, and how the efforts made by law enforcement agencies to overcome the occurrence of theft with violence using sharp weapons. This research was conducted in a normative law conducted in this study using a normative juridical approach, namely by analyzing problems and research through approaches to legal principles that refer to norms. Data obtained in this study will be analyzed using qualitative normative methods with the material or material used in this thesis obtained through library research, namely from the book. Based on the analysis of the data and facts, the authors conclude, among others: factors that influence the occurrence of crime of theft by violence using sharp weapons, namely the low level of education of the perpetrators and criminal behavior of the perpetrators themselves (internal factors) does not support the fulfillment of the life needs of the perpetrators, social environmental factors, and weak law enforcement factors. The reason for the perpetrators of using sharp weapons is to make it easier to carry out their actions, to threaten their victims so that they feel afraid and hand over their property and protect themselves. Efforts made by law enforcement officials are preventive and repressive efforts. Preventive measures taken by the Police are conducting counseling and patrolling. Repressive efforts are actions for criminals through a criminal justice process and conducting guidance in a prison institution. Keywords : Crime, theft, violence, sharp weapons, preventive and repressive.